Overview of Circular Economy Indicators in the City: Bratislava - Jorgic, Bojan; Mihaľová, Paulína (Studia Ecologiae et Bioethicae, 2026)
The transition from a linear to a circular economic model is a critical response to the environmental, social, and economic challenges facing urban areas. This study examines the role of cities, particularly Bratislava, in implementing circular economy principles. It highlights the need for appropriate indicators to assess circularity at the municipal level. Drawing upon a comprehensive review of academic literature, strategic municipal documents, and direct consultations with stakeholders, the study proposes a set of 27 indicators grouped into three core dimensions: environmental, economic-financial, and cultural-social. These indicators reflect key areas such as waste management, resource efficiency, public procurement, and citizen engagement. The indicators are further categorized into three priority levels (A–B–C) based on their relevance and data availability. The results reveal both promising trends—such as decreasing municipal waste landfilling rates—and persistent challenges, including insufficient recycling rates and data limitations in sectors such as energy and procurement. The absence of a unified methodological framework for monitoring circular economy progress at the city level remains a major obstacle. The study highlights the necessity of developing standardized and context-sensitive indicator systems that allow cities to systematically track, compare, and improve their circular strategies. The findings underscore the importance of continued interdisciplinary research and collaboration among public institutions, academia, and society in advancing the circular economy agenda.